2022
DOI: 10.3390/ijms23074023
|View full text |Cite
|
Sign up to set email alerts
|

Oral Toxicokinetics, Tissue Distribution, and 28-Day Oral Toxicity of Two Differently Manufactured Food Additive Silicon Dioxides

Abstract: (1) Background: Synthetic amorphous silica (SAS) is widely used as a food additive and contains nano-sized particles. SAS can be produced by fumed and precipitated methods, which may possess different physiochemical properties, toxicokinetics, and oral toxicity. (2) Methods: The toxicokinetics of fumed SAS and precipitated SAS were evaluated following a single-dose oral administration in rats. The tissue distribution and fate of both SAS particles were assessed after repeated oral administration in rats for 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Silicon dioxide has water/oil adsorption properties, which cause dehydration of the cell membrane of PRM after absorbing lipids from their cuticle ( Schulz et al, 2014 ). One of the advantages of silica products is their low oral toxicity ( Yoo et al, 2022 ).…”
Section: Physical Control By Inorganic Materialsmentioning
confidence: 99%
“…Silicon dioxide has water/oil adsorption properties, which cause dehydration of the cell membrane of PRM after absorbing lipids from their cuticle ( Schulz et al, 2014 ). One of the advantages of silica products is their low oral toxicity ( Yoo et al, 2022 ).…”
Section: Physical Control By Inorganic Materialsmentioning
confidence: 99%
“…Our previous research reported the oral toxicokinetics of fumed and precipitated SiO 2 particles after a single-dose administration to rats, showing ~3.1% and ~3.9% absorption for the former and the latter, respectively [13]. Tissue distribution patterns demonstrated that both SiO 2 particles accumulated in only the liver at 28 d following repeated oral administration of 2000 mg/kg to rats for 28 d [13].…”
Section: Introductionmentioning
confidence: 98%
“…Our previous research reported the oral toxicokinetics of fumed and precipitated SiO 2 particles after a single-dose administration to rats, showing ~3.1% and ~3.9% absorption for the former and the latter, respectively [13]. Tissue distribution patterns demonstrated that both SiO 2 particles accumulated in only the liver at 28 d following repeated oral administration of 2000 mg/kg to rats for 28 d [13]. Notably, a significantly higher accumulation of precipitated SiO 2 than fumed SiO 2 was found in the liver, but the elevated levels returned to normal basal levels at 1 d of the recovery period [13].…”
Section: Introductionmentioning
confidence: 98%
“…Determining whether SiO 2 and TiO 2 are present as intact particles, aggregates, or dissolved forms is important to understand and predict their potential toxicity. Orally taken SiO 2 is generally considered to be not toxic at actual usage levels [17][18][19]. However, some contradictory results were also reported, showing its potential toxicity in terms of oxidative stress, inflammation response, and intestinal barrier dysfunction, although most studies were performed using in vitro systems [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study, we developed a Triton X-114 (TX-114)-based CPE method to separate zinc oxide (ZnO) particles as intact forms from com-mercial foods and biomatrices without pre-treatments [14]. The CPE approach was also developed for SiO 2 in biomatrices and its fates were determined in cell lines and tissues [17]. In this study, the CPE method was further optimized for the most widely applied food additive particles, SiO 2 and TiO 2 , in food matrices to determine their dissolved, aggregated, or particle fates in commercial food products.…”
Section: Introductionmentioning
confidence: 99%